Salt balance, fresh water residence time and budget for non-conservative materials for Makoba bay during wet season - Ngusaru , AS; Mmochi , AJ (Tanzania Journal of Science, 2021)
Water and salt budgets suggest that in order to balance the inflow and outflow of water at Makoba bay, there is net flux of water from the bay to the open ocean during wet season. Residual salt fluxes between the bay and the open ocean indicate advective salt export. Exchange of water between the bay with the open ocean plays a role of replacing exported salt via mixing. Calculated freshwater residence time for the bay is 63 days during wet season. Budget results for non-conservative materials indicate net DIP flux from the ocean to the bay and a net DIN flux from the bay to the open ocean. Therefore Makoba Bay acts as a sink for dissolved inorganic phosphorus and a source of dissolved inorganic nitrogen during wet season. Stoichiometry calculations suggest that the bay is net autotrophic and fixing nitrogen during the wet season.